The Economics and Implications of Data : An Integrated Perspective - Carriere-Swallow, Yan.; Haksar, Vikram (Washington, D.C. : International Monetary Fund, 2019)
This SPR Departmental Paper will provide policymakers with a framework for studying changes to national data policy frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet